Islamizing engineering curriculum - Shuriye, Abdi Omar (Future Text Publications, 2006)
There exists exclusionist methodolory in the way Muslim scholarship developed its approach to scientiflc knowledge and its relation to shari'ah sciences or Islamic ontology. The realm of scientific i<nowledge has been dichotomously excluded from the ambit of revelation due to the Western traditions in the educational system adhered to by the Muslim world. In this Western approach to education, revelation is considered baseless metaphysics and rival to science, and the latter, being the only truth, is confined to empiricism, pure human reasoning and considered transcendental in the affairs or the study of nature. The two however should not be alienated as scientific activities emanates from an ontological outlook through the individual endeavors and on the strength of the inter connection between the two. On balance, scientists, in most cases, presuppose natural laws or divine intervention that goverrr and regulate the behavior of natural objects; which they normally acknowledge prior to their engagement in arry empirical activity. My contention in this paper is to establish the compatibility of the two streams, science and religion, as the justi$ring evidence of both holds identical caliber, an account that indicates the impossibility of ones existence without the other. Therefore the denial outlook addressed, by various scholars of the revealed and the man made scientific, should be attributed to the lack of faith in the revelation, on the part of those who projected the division. Hence, the perception that the scientiflc inquiry; in its most generic sense; is an inherently innovative activitv that erpetually disturbs religious, ethical and societal values must Lre subjected to corrective filtration. It has been the argument of the dorninant Western scientists and sizeable Muslim scholars that if science is to prosper, its inquiry has to be f,i-ee fi onl religious, political anC etkrical censorships; this view however echoes the inherent scientific tradition of the West, as aforementioned" The revelation invites scientiflc reasoning and in numerous dictums presumes that the nature is a rational order which is coherently a predictable domain; and man is capable of comprehending the attitude of the nature as it made rnalleable to him. This attitude of the revelation bestows man and encourages an open ended scientiflc inquiry, which ensures that human personality grows with positive values, attitudes, training and continuous learning of relevant knowledge. Having said the aforementioned, it should also be noted that the process of training a Muslim engineer to meet the organizational demands is a coninuous concerrl, as personal development comes from the extent of training one receives; added to it, is the fact that positive attitudes and skills are prerequisite for the development of holistic engineers; hence reloaded curriculum should emphasize the realization of some core aspects of human development in addressing the role of Muslirn engineers who will mostly be in a purely profit making institutiorrs o.ild organizations. Reloaded curriculum converge professional standards and internalized ethical values; covering:1 IsLamtc uirtues required of a Muslim engineer; this includes sincerity gratefulness, moderation, discipline, consistency, accountability, and cooperation 2 Human deuelopment; this aspect of the curriculum focuses human values, engineering ethics, ecological ethics, resource management, competitiveness, challenges, efficiency, effectiveness, and productivity. 3 Deciston maktng; this personal quality requires knowledge, professionalism, and strategies.